2017
DOI: 10.1002/mgg3.250
|View full text |Cite
|
Sign up to set email alerts
|

Independent variant analysis of TEAD1 and OCEL1 in 38 Aicardi syndrome patients

Abstract: BackgroundAicardi syndrome is a severe neurodevelopmental disorder characterized by infantile spasms, typical chorioretinal lacunae, agenesis of the corpus callosum, and other neuronal migration defects. It has been reported recently that de novo variants in TEAD1 and OCEL1 each may cause Aicardi syndrome in a single individual of a small cohort of females with this clinical diagnosis. These data were interpreted to suggest that the clinical diagnosis of Aicardi syndrome may be genetically heterogeneous.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A study identified a TEAD1 variant in one individual with Aicardi syndrome, out of a cohort of ten (Schrauwen et al, 2015). In contrast, a second study consisting of 38 individuals did not identify any TEAD1 variants (Wong et al, 2017). Modelling this mutation in rodent models could enable researchers to determine whether this TEAD1 variant contributes to Aicardi-related phenotypes in mice.…”
Section: Dysregulation Of Teads Results In Cancer and Other Diseasesmentioning
confidence: 99%
“…A study identified a TEAD1 variant in one individual with Aicardi syndrome, out of a cohort of ten (Schrauwen et al, 2015). In contrast, a second study consisting of 38 individuals did not identify any TEAD1 variants (Wong et al, 2017). Modelling this mutation in rodent models could enable researchers to determine whether this TEAD1 variant contributes to Aicardi-related phenotypes in mice.…”
Section: Dysregulation Of Teads Results In Cancer and Other Diseasesmentioning
confidence: 99%
“…It was previously thought to be caused by mutations in the TEAD1 (11p15.3; MIM 189967) gene. However, in 2017, a study on 38 AIC subjects identified the TEAD1 variant in only one patient, which suggested the contribution of other genes in the development of this condition [ 39 ]. Due to the lack of precise genetic or molecular possibilities for AIC identification, the diagnosis is mainly based on imaging and clinical symptoms, particularly disc anomalies (drusen, pigmented and morning glory discs) [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in most of our patients with the most severe basal ganglia dysmorphisms, genetic analysis excluded tubulinopathies. 23 Karyotype analysis, 3 investigation of candidate genes (FLNA, TEAD1, OCEL1), [24][25][26] methylation array, 27 and, more recently, advanced genetic analysis in the form of exome sequencing, 23 carried out by different research groups, have thus far failed to solve the genetic puzzle of AIC. The severe and diffuse involvement of multiple brain structures observed in our large cohort resembles the broad spectrum of findings in tubulinopathies.…”
Section: Discussionmentioning
confidence: 99%